Navigating Intensive Motherhood: Inventiveness and Agency Among Low-Income Single Mothers - Hašková, Hana; Dudová, Radka (Socialinė teorija, empirija, politika ir praktika, 2025)
This article explores how the ideology of intensive motherhood is reflected in, and shapes, the experiences of low-income single mothers in Czechia. By focusing on this group, the study advances understanding of the diffusion of the intensive motherhood ideology and the intersectional aspects of social reproduction. We demonstrate that, while intensive motherhood norms influence maternal practices in Czechia, low-income single mothers respond with inventive adaptations and reframing that reflect their specific circumstances. These forms of agency of low-income single mothers are often overlooked when their mothering is viewed solely through the lens of resource deficits relative to the dominant norms. Despite precarious conditions, these mothers maintain a positive maternal identity and dignity by adapting, reframing, or, at times, challenging the prevailing norms of intensive mothering. Our findings show that, in striving to meet the dominant norms, low-income single mothers undertake a range of additional, highly emotion-, labour- and time-intensive activities on a daily basis, yet these activities remain unrecognised in traditional conceptualisations of intensive motherhood, which are largely based on white middle-class women. In the neoliberal context, however, these unacknowledged efforts contribute to their further marginalisation.